INTERGRASI MULTIKULTURAL DALAM MASYARAKAT MULTIETNIS (JAWA,CINA DAN ARAB KETURUNAN)DI KOTA SEMARANG - Quway, Nabila (IJTIMAIYA: Journal of Social Science and Teaching, 2018)
Indonesia, which consists of a variety of different ethnicities, can be said to be a multiethnic country. In such a society, cultural integration is needed in order to create a condition of society that respects cultural differences. The concept of integration is closely related to the mulltulturalism view of the acculturation process that takes place in the form of every ethnic effort to learn other cultures without losing their culture. In Integration, the three ethnic groups respect and respect other ethnic cultures. There was no response that the culture of one ethnic group was higher than other ethnic groups. Even so, there are still slanted responses from one ethnic group to another.Keywords: Intergrasi, Multicultural, Multietnis, Semarang